2020
DOI: 10.1111/ajag.12815
|View full text |Cite
|
Sign up to set email alerts
|

What makes community‐based physical activity programs for culturally and linguistically diverse older adults effective? A systematic review

Abstract: This integrative review aimed to determine the features of effective physical activity programs for culturally and linguistically diverse (CALD) older adults. Methods: We searched for relevant articles in MEDLINE, PubMed, Google Scholar, Scopus and CINAHL. Articles were selected for evaluation if they included CALD older adults and implemented physical activity programs with culturally specific design features. Consistent with the Whittemore and Knafl integrative review methodology, we used the Downs and Black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…When discussing ways for making programs more inclusive and accessible, some participants suggested targeted programs (e.g., graded classes, women’s only programs). This is consistent with previous studies which found that positive experiences at recreation centres can be cultivated by providing specialised classes for persons living with disabilities [ 39 ], introductory and graded classes for older adults [ 16 ], culturally-familiar programs instructed in native languages for CALD persons [ 53 ], women’s only classes [ 52 ], and trans-specific and gender non-conforming classes for LGBTQIA + individuals [ 32 ]. Several participants, especially those living with a disability, identified instructor training around adaption of programs to accommodate various levels and abilities as a means for improving accessibility and inclusion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When discussing ways for making programs more inclusive and accessible, some participants suggested targeted programs (e.g., graded classes, women’s only programs). This is consistent with previous studies which found that positive experiences at recreation centres can be cultivated by providing specialised classes for persons living with disabilities [ 39 ], introductory and graded classes for older adults [ 16 ], culturally-familiar programs instructed in native languages for CALD persons [ 53 ], women’s only classes [ 52 ], and trans-specific and gender non-conforming classes for LGBTQIA + individuals [ 32 ]. Several participants, especially those living with a disability, identified instructor training around adaption of programs to accommodate various levels and abilities as a means for improving accessibility and inclusion.…”
Section: Discussionsupporting
confidence: 91%
“…Key communication needs identified in this study included having more accessible and inclusive signage (e.g., bigger font on signs for those with vision impairment, multilingual signage) and information provision. This parallels previous research, which has shown that recreation centre use can be facilitated by providing information in other languages [ 52 , 53 ], distributing information about programs and services targeting specific cohorts [ 16 ], and having marketing materials and signage that reflect priority populations (e.g., informative advertisement of inclusion-centred spaces with images of LGBTQIA + people) [ 32 , 39 , 49 ]. Further, a systematic review indicated that signage/information for accessible routes in and around centres and alternative means of accessible information (e.g., braille, large print or audio brochures, tactile cues about location) are important for ensuring that fitness centres are accessible for people living with disabilities [ 27 ].…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, the provision of culturally responsive healthcare services to ameliorate Chinese late‐life immigrants’ loneliness and social isolation remains a common challenge for nurses (Stewart et al, 2011) and has not been well addressed (Zhao et al, 2020). It is imperative that healthcare services are designed to match older people's cultural perspectives, values and language needs, and maximised to reduce their barriers to accessing services (Montayre et al, 2020). However, many studies fail to distinguish late‐life immigrants from those who immigrated earlier in life and aged in the host country.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors, such as social support, personal, and community motivation to engage, need to be encouraged [19]. Implementation of intervention programs that take into account cultural diversity may improve engagement in nonpharmacological strategies, for example, physical therapies [25], medication adherence, and vascular risk factor control [4] with consequent reduction in cerebrovascular disease burden.…”
Section: Discussionmentioning
confidence: 99%